2020
DOI: 10.3390/su12041616
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Dynamic Properties of Clay–Gravel Mixtures at Low Strain Level

Abstract: In order to support the dynamic design of subgrade filling engineering, an experiment on the dynamic shear modulus (G) and damping ratio (D) of clay-gravel mixtures (CGMs) was carried out. Forty-two groups of resonant column tests were conducted to explore the effects of gravel content (0%, 10%, 20%, 30%, 40%, 50%, and 60%, which was the mass ratio of gravel to clay), gravel shape (round and angular gravels), and confining pressure (100, 200, and 300 kPa) on the dynamic shear modulus, and damping ratio of CGMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Scanning by X-ray [4,43] can identify the internal characteristics of the rocks inside the slope without damage. On the basis of scanning images, the rocks' and cracks' locations in soil-rock mixtures are obtained directly, which is meaningful for evaluating the mechanical properties of soil-rock mixtures and establishing soil-rock slope models.…”
Section: Discussion About Characteristic Parameters Of the Soil-rock mentioning
confidence: 99%
“…Scanning by X-ray [4,43] can identify the internal characteristics of the rocks inside the slope without damage. On the basis of scanning images, the rocks' and cracks' locations in soil-rock mixtures are obtained directly, which is meaningful for evaluating the mechanical properties of soil-rock mixtures and establishing soil-rock slope models.…”
Section: Discussion About Characteristic Parameters Of the Soil-rock mentioning
confidence: 99%
“…Hence, suitable rock size is important in the analysis of soil-rock mixtures. According to the sample preparation standard (GB/T 50123-1999) and existed references [1,33,34], Kalender et al [2,8,35,36] concluded that, in soil-rock mixtures, minimum thresholds for soil and rock are suggested to be the minimum value of 2 mm and 0.05 Lc (where Lc is the characteristic length of model), and maximum thresholds are advised to be 0.2 Lc. Based on the advice, Zhang et al [1] conducted triaxial tests with soil-rock mixtures containing 2-10 mm rocks (samples are 50 mm in diameter and 100 mm in height) and obtained good experimental results.…”
Section: Size Characteristic Of Rocksmentioning
confidence: 99%
“…For better analysis of rock distribution characteristics in soil-rock slopes, 6 groups of soil-rock mixture samples were made consisting of different rock shapes (angular and round) and contents (10%, 30%, and 60%). e specimens were cylindrical in shape with diameter 50 mm and height 100 mm and each layer was compacted 20 [1,34,38], rock size in specimen was defined to be between 2 and 10 mm. CT [39] is a good method to observe the internal structures of objects without any disturbance and has been widely utilized in medicine and engineering.…”
Section: Rock Distribution Characteristics In Soil-rock Mixturesmentioning
confidence: 99%
“…In order to ensure a working energy supply, China's coal mining has been gradually promoted to the deep rock strata [1][2][3]. The process of deep coal resource mining will inevitably produce a large mining response.…”
Section: Introductionmentioning
confidence: 99%